The Effect of Prebiotic Consumption on the Gastrointestinal Microbiota of Healthy Adults: A Randomized, Controlled, Crossover Trial (P20-015-19) - Krug, Annemarie (Curr Dev Nutr, 2019)
OBJECTIVES: Chronic stress is recognized as a contributing factor in health conditions such as depression, anxiety, and sleep disturbances. Prebiotic consumption, which changes the gastrointestinal microbiota in a way that benefits host health, is one potential treatment being explored to alleviate these conditions. Accordingly, we aimed to determine the effects of fructooligosaccharide (FOS) and galactooligosaccharide (GOS) consumption on changes in the gastrointestinal (GI) microbiota and biological and behavioral markers of stress among adults. METHODS: A randomized, controlled, double-blind, crossover trial was conducted in healthy adults (n = 24) between 25 and 45 years of age. Participants consumed two study beverages in a counter balanced order: 1) 8 oz per day 1% Lactaid (control) and 2) 8 oz of 1% Lactaid with 5 g FOS and 5 g GOS (prebiotic). Each study beverage was consumed daily for 4-weeks with a 2 to 4-week washout between study periods. Fecal samples were collected at the beginning and end of each period. Following fecal DNA extraction, the V4 region of the 16S rRNA gene was amplified. Sequencing was performed on an Illumina HiSeq. Sequence data were analyzed with DADA2 and QIIME 2. Taxonomy was assigned with the GreenGenes 13_8 99% OTU reference database. Statistical analyses were conducted in SAS 9.4 using linear mixed modeling with time, treatment, and the time by treatment interaction as fixed effects and participant and period as random effects. RESULTS: Prebiotic consumption increased the relative abundance of Bifidobacterium (P = 0.01) compared to the control group. In addition, there was an increase observed in the relative abundance of Erysipelotrichaceae Clostridium (P = 0.04) in the prebiotic group and a decrease in the control group. In contrast, there was a decrease observed in the relative abundance of Prevotella (P = 0.004) in the prebiotic group and an increase in the control group. CONCLUSIONS: These results demonstrate that FOS and GOS induce changes in the GI microbiota of healthy adults. Ongoing analyses include an examination of the relationships between 24-hour urinary free cortisol concentrations, a potential biological marker of stress, and relative abundance of microbes examined in the current study. FUNDING SOURCES: USDA National Institute of Food and Agriculture, Hatch project 1009249.